Pengaruh Pembelajaran Blended Learning Terhadap Perkembangan Emosional Anak Usia Dini - Norlinda Kudji; Fifti Yundi Selan; Adeleide Lasboy; Englintan Dethan; Mesi Reinammah; Dance Babis; Asaria Kamesa; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Emotional development is an important aspect in supporting early childhood’s ability to adapt, interact, and manage emotions in the learning process. One learning model that is widely implemented today is d-blended learning, which is a combination of online and offline learning. This study aims to determine the effect of blended learning on the emotional development of early childhood. The research method used was quantitative with an ex-post facto research design. The research subjects consisted of 15 children aged 5–6 years at PAUD Saenam Binlaka, selected using a total sampling technique. Data were collected using a Likert-scale questionnaire measuring aspects of emotional regulation, emotional expression, and children’s social relationships in blended learning. Data analysis was conducted using simple linear regression with the assistance of SPSS 25.0. The results showed that blended learning had a positive and significant effect on the emotional development of early childhood, with a significance value of p = 0.009 (< 0.05) and a coefficient of determination of 0.411%. This indicates that the proper implementation of blended learning can support children’s ability to manage emotions, express feelings, and build positive social relationships. Therefore, d-blended learning can be an effective alternative learning strategy to support the emotional development of early childhood.